Políticas públicas e agroecologia: os programas estatais de aquisição de alimentos e a reprodução social dos associados à Cooperativa Mista de Produção Camponesa de Comercialização do Paraná CPC-PR - Silva, Jeferson Luis da (2016)
The theme of the survey dealt with the public policy called Food Acquisition Program (PAA) and the National School Meal Program (PNAE) as a way of promoting Agroecology, analyzing the contribution of such policies for the social reproduction of peasant agriculture. The effects of public policies for the promotion of family farming as a whole does not automatically imply the promotion of Agroecology in this sense the research problem was guided to analyze the social reproduction of peasant farmers associated with CPC-PR which is part of the derived agricultural income the institutional market promoted by públicas.Esta analysis policies used to check the value and agricultural income. To meet the proposed objectives initially analyzed the relationship between the public sector and the production of value and wealth. In this sense we analyze the family and peasant farming mainly in the social differentiation between them to identify their relations with Agroecology through diversification and tend to the preservation of natural resources. From these assumptions we tried to make an analysis of the compatibility of food procurement policies to promote agroecology in peasant agriculture. For such public policies analyzed were the PAA and PNAE and the effect of agricultural income (obtained by access to programs) in the social reproduction of the surveyed farmers. The method adopted was the diagnostic analysis of agrarian systems (ADSA), which is characterized by prioritizing the explanation at the expense of description, to value the historical approach, strive for heterogeneity of reality trying to observe the agriculture differentiation process and analyzing each production unit making an overview of the comprehensive analysis and analyzing the more specific levels. This method is consistent with the analysis of complex agricultural problems situations, which can not be summarized in order to establish standards outside the local reality, and historical trajectory which the phenomenon is inserted. Also its use is related to analysis and intervention of the government, being consistent with the proposal of this research. It was found that the institutional market is important for the social reproduction of peasant agriculture. In this sense the state is able to generate value for society and wealth by promoting agroecology through peasant agriculture, its production characteristics with tendency to diversification and preservation of nature. Being thus promoting social reproduction of peasant agriculture central to building a viable sustainable development model.